High-strength wear-resistant nylon and processing technology thereof

By using the composite formula of enhanced polyacide resin and nano -grade wear -resistant additives in nylon materials, and use double screw extrusion molding process, solve the problem of low strength and low wear resistance of nylon materials, realize high strength and high and high height The effect of abrasion resistance.

CN119371815APending Publication Date: 2025-01-28CHANGSHA ZHONGJING MACHINERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411554957.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing nylon materials are limited by low strength and low wear resistance in high demand occasions, making it difficult to simultaneously improve the strength and wear resistance of the material.

Method used

The composite formula of enhanced polyacide resin and nano -grade wear -resistant additives is adopted, and high -strength wear -resistant nylons are prepared through dual screw extrusion.

Benefits of technology

The high abrasion and high strength of the nylon material is realized, and the stability of the material in the high temperature environment is ensured, and the material is abrasion resistance and mechanical strength through uniformly dispersed nanoparticles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371815A_ABST
    Figure CN119371815A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material science and polymer engineering, and discloses high-strength wear-resistant nylon and a processing technology thereof, and the nylon comprises the following raw materials by weight: 20-23 parts of carbon fiber reinforced PA; 11-14 parts by weight of E type glass fiber reinforced PA; 3-5 parts by weight of bio-based furan acyl chloride derived aromatic polyamide resin; 6-8 parts by weight of a polyether ester amide block copolymer; 1.1 to 1.3 parts by weight of PA filled with talcum powder; 1.5 to 2.0 parts by weight of montmorillonite powder; 0.30 to 0.36 part by weight of aramid fiber powder; 0.16 to 0.20 part by weight of an antioxidant 1098; according to the invention, a composite formula of the enhanced polyamide resin and the nano-scale wear-resistant additive is adopted in the raw material formula, and the nylon finished product is prepared from the raw material formula through the processing technology disclosed by the invention, so that compared with a nylon product prepared by a traditional technology, the nylon finished product prepared by the technology disclosed by the invention has the advantages that the hardness is high; not only are the dispersibility and integration improved, but also the molecular distribution of the nylon finished product is more uniform, and the mechanical property reaches the optimal state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and polymer engineering technology, in particular to high-strength wear-resistant nylon and a processing technology thereof. Background Art

[0002] Although existing nylon has good toughness, fatigue resistance and corrosion resistance, its low strength and low wear resistance limit its application in certain high-demand occasions. In order to overcome these shortcomings, researchers have adopted a variety of modification techniques, including physical modification and chemical modification. Physical modification usually involves adding various fillers such as fibers, inorganic particles, etc., while chemical modification improves material properties through methods such as block and graft copolymerization. However, these methods often sacrifice the performance of another aspect while improving the performance of one aspect, such as improving wear resistance while reducing the toughness of the material.

[0003] As technology advances, new nylon formulations and preparation processes have been developed to improve both the material's strength and wear resistance. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies of the prior art, the present invention provides high-strength wear-resistant nylon and a processing technology thereof, which have the advantages of high wear resistance and high strength, and solve the problems of low strength and low wear resistance of nylon in the prior art.

[0006] (II) Technical solution

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: high-strength wear-resistant nylon, wherein the raw materials of the nylon and their weight parts are: 20-23 weight parts of carbon fiber reinforced PA; 11-14 weight parts of E-glass fiber reinforced PA; 3-5 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 6-8 weight parts of polyether ester amide block copolymer; 1.1-1.3 weight parts of talc filled PA; 1.5-2.0 weight parts of montmorillonite powder; 0.30-0.36 weight parts of aramid powder; 0.16-0.20 weight parts of antioxidant 1098; 0.56-0.62 weight parts of coupling agent.

[0008] Preferably, the carbon fiber reinforced PA, E-glass fiber reinforced PA and talc-filled PA together constitute a reinforced polyamide resin, and the montmorillonite powder, manganese powder and aramid powder together constitute a nano-level wear-resistant additive, and the particle size is between 80-100 nanometers.

[0009] Preferably, the synthesis process of the bio-based furanoyl chloride derived aromatic polyamide resin is:

[0010] S1.1, conducting a low-temperature solution polycondensation reaction of bio-based 2,5-furandicarbonyl chloride and 3,4'-diaminodiphenyl ether in a solvent volume ratio of 1:2 in 5-6 volumes of N,N-dimethylacetamide at 5-8°C;

[0011] S1.2. After the reaction is complete, the obtained resin solution is spun through a dry-jet wet spinning device using dry-jet wet spinning technology to prepare aromatic polyamide fibers containing furan rings.

[0012] Preferably, the polyetheresteramide block copolymer is formed by connecting polyether and polyamide blocks through chemical bonds, and has a shrinkage rate of 0.5%-1.5%.

[0013] Preferably, the processing technology of high-strength wear-resistant nylon is prepared according to the weight parts of the above-mentioned high-strength wear-resistant nylon raw materials, comprising the following steps:

[0014] Step 1, raw material preparation: prepare raw material formula weight parts of bio-based furanyl chloride derived aromatic polyamide resin, polyether ester amide block copolymer, montmorillonite powder, manganese powder and aramid powder;

[0015] Step 2, drying the raw materials: drying the bio-based furanyl chloride-derived aromatic polyamide resin and the polyether ester amide block copolymer;

[0016] Step 3, mixing: uniformly mixing the dried bio-based furanoyl chloride-derived aromatic polyamide resin and the polyetheresteramide block copolymer with montmorillonite powder, manganese powder and aramid powder;

[0017] Step 4: Extrusion molding: using a twin-screw extruder for melt extrusion molding;

[0018] Step 5: Extrusion process parameters: adjust the screw speed, feed screw speed, screw and barrel temperature and feed rate parameters;

[0019] Step 6: Cooling and solidification: The molten material after extrusion is cooled and solidified through an air cooler to form the nylon shape designed by the manufacturer;

[0020] Step 7. Post-processing: cutting, grinding or secondary processing of the extruded nylon according to the shape of the nylon;

[0021] Step 8. Performance testing: Conduct flame retardant grade test, high temperature tensile test, compression modulus, impact elasticity, peel strength, moisture content, hardness, heat deformation temperature, melt index, thickness, combustion performance, compression permanent deformation and whiteness test on the manufactured nylon.

[0022] Preferably, in step 2, the raw materials are dried: the bio-based furanoyl chloride-derived aromatic polyamide resin is dried at 90-100° C. for 4-5 hours, and the polyetheresteramide block copolymer is dried at 120-135° C. for 2-3 hours.

[0023] Preferably, the stirring conditions of step three are: the stirring temperature is controlled at 50-60° C., the stirring speed is controlled at 200-250 r / min, and the stirring time is controlled at 1.5-3 hours.

[0024] Preferably, the parameters of the twin-screw extruder melt extrusion molding in step 4 are set as follows: the extrusion temperature is controlled at 280-295°C, the pressure is controlled at 18-20MPa, and the shear rate is controlled at 300-400s -1 .

[0025] Preferably, the extrusion process parameters in step five are set as follows: screw speed is 450-500r / min, feeding screw speed is 40-50r / min, screw temperature is 165°C-175°C, barrel temperature is 295°C-300°C, and feeding rate is 16-20kg / h.

[0026] Preferably, in step 6, cooling and curing are performed using an air cooler, and the parameters of the air cooler are set as follows: cooling capacity is 100kW; cooling water volume is set to 42-48m 3 / h; air flow rate is set to 4.35-4.45m 3 / h; the inlet water temperature is set to 20℃~22℃.

[0027] Compared with the prior art, the present invention provides high-strength wear-resistant nylon and its processing technology, which has the following beneficial effects:

[0028] 1. The present invention adopts a composite formula of enhanced polyamide resin and nano-level wear-resistant additive in the raw material formula. Since the heat deformation temperature of the enhanced polyamide resin is relatively high, the nylon finished product can still maintain the stability of its shape and size under high temperature environment and is not easy to deform. The nano-level wear-resistant additive has high hardness and high wear resistance due to its nano-level particle size, so that the additive can form hard particles in the nylon matrix, effectively resisting wear and scratches, and extending the service life of the product. At the same time, the nanoparticles can be evenly dispersed in the nylon matrix, avoiding the problem of uneven performance caused by agglomeration of traditional fillers. This uniform dispersion ensures that the product has consistent wear resistance in all directions. The combination of the two materials not only improves the dispersibility and fusion of the nylon finished product, but also increases the wear resistance and mechanical strength of the nylon finished product.

[0029] 2. The present invention adopts a twin-screw extrusion molding process, and then controls the temperature, pressure and shear rate of the twin-screw extruder within a preset range, which helps to control the rheological properties of the material, so that the molecular distribution of the nylon finished product is more uniform and the mechanical properties are optimized. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] See also Figure 1 , high-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 20-23 weight parts of carbon fiber reinforced PA; 11-14 weight parts of E-glass fiber reinforced PA; 3-5 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 6-8 weight parts of polyether ester amide block copolymer; 1.1-1.3 weight parts of talc filled PA; 1.5-2.0 weight parts of montmorillonite powder; 0.30-0.36 weight parts of aramid powder; 0.16-0.20 weight parts of antioxidant 1098; 0.56-0.62 weight parts of coupling agent.

[0033] Specifically, carbon fiber reinforced PA, E-glass fiber reinforced PA and talc-filled PA together constitute reinforced polyamide resin, montmorillonite powder, manganese powder and aramid powder together constitute nano-level wear-resistant additives, and the particle sizes are all between 80-100 nanometers.

[0034] Reinforced polyamide resin: Reinforced polyamide resin has a high heat deformation temperature. In a high temperature environment, the material can maintain the stability of its shape and size, is not easy to deform, and has good fluidity in the molten state, making it easier for the nylon finished product to fill the mold during the extrusion molding process.

[0035] Nano-level wear-resistant additives: The nano-level particle size of nano-level wear-resistant additives has high surface hardness and wear resistance, which enables the additives to form hard particles in the nylon matrix, effectively resisting wear and scratches, and extending the service life of the product. In addition, the nanoparticles can be evenly dispersed in the nylon matrix, avoiding the uneven performance problem caused by agglomeration of traditional fillers. This uniform dispersion ensures that the nylon finished product has consistent wear resistance in all directions.

[0036] The synthesis process of bio-based furanoyl chloride derived aromatic polyamide resin is as follows:

[0037] S1.1, conducting a low-temperature solution polycondensation reaction of bio-based 2,5-furandicarbonyl chloride and 3,4'-diaminodiphenyl ether in a solvent volume ratio of 1:2 in 5-6 volumes of N,N-dimethylacetamide at 5-8°C;

[0038] S1.2. After the reaction is complete, the obtained resin solution is spun through a dry-jet wet spinning device using dry-jet wet spinning technology to prepare aromatic polyamide fibers containing furan rings.

[0039] Specifically, the polyetheresteramide block copolymer is formed by connecting polyether and polyamide blocks through chemical bonds, and has a shrinkage rate of 0.5%-1.5%.

[0040] Specifically, the processing technology of high-strength wear-resistant nylon is prepared according to the weight parts of the above-mentioned high-strength wear-resistant nylon raw materials, comprising the following steps:

[0041] Step 1, raw material preparation: prepare raw material formula weight parts of bio-based furanyl chloride derived aromatic polyamide resin, polyether ester amide block copolymer, montmorillonite powder, manganese powder and aramid powder;

[0042] Step 2, drying of raw materials: drying the bio-based furanoyl chloride-derived aromatic polyamide resin and the polyetheresteramide block copolymer to remove moisture and ensure the fluidity and reactivity of the mixture. This step is to prevent bubbles and unevenness in subsequent processing;

[0043] Step 3, mixing: the dried bio-based furanoyl chloride-derived aromatic polyamide resin and polyetheresteramide block copolymer are mixed evenly with montmorillonite powder, manganese powder and aramid powder to ensure that the materials are mixed evenly. This step is to ensure that all ingredients can be fully integrated to improve the overall performance of the material;

[0044] Step 4: Extrusion molding: Use a twin-screw extruder for melt extrusion molding to control the rheological properties of the material;

[0045] Step 5. Extrusion process parameters: Adjusting the screw speed, feed screw speed, screw and barrel temperature and feed rate parameters will help optimize the mixing, plasticizing and extrusion efficiency of the material;

[0046] Step 6: Cooling and solidification: The molten material after extrusion is cooled and solidified through an air cooler to form the nylon shape designed by the manufacturer;

[0047] Step 7. Post-processing: Cut, grind or perform secondary processing on the extruded nylon according to its shape; this step is to meet specific application requirements and improve the accuracy and surface quality of the product;

[0048] Step 8. Performance testing: Conduct flame retardant grade test, high temperature tensile test, compression modulus, impact elasticity, peel strength, moisture content, hardness, heat deformation temperature, melt index, thickness, combustion performance, compression permanent deformation and whiteness test on the manufactured nylon.

[0049] Specifically, in step 2, the raw materials are dried: the bio-based furanoyl chloride-derived aromatic polyamide resin is dried at 90-100° C. for 4-5 hours, and the polyetheresteramide block copolymer is dried at 120-135° C. for 2-3 hours.

[0050] Specifically, the stirring conditions of step three are: the stirring temperature is controlled at 50-60° C., the stirring speed is controlled at 200-250 r / min, and the stirring time is controlled at 1.5-3 hours.

[0051] Specifically, the parameters of the twin-screw extruder melt extrusion molding in step 4 are set as follows: the extrusion temperature is controlled at 280-295°C, the pressure is controlled at 18-20MPa, and the shear rate is controlled at 300-400s -1 .

[0052] Specifically, the extrusion process parameters in step five are set as follows: screw speed is 450-500r / min, feeding screw speed is 40-50r / min, screw temperature is 165°C-175°C, barrel temperature is 295°C-300°C, and feeding rate is 16-20kg / h.

[0053] Specifically, in step 6, an air cooler is used for cooling and curing, and the parameters of the air cooler are set as follows: cooling capacity is 100kW; cooling water volume is set to 42-48m 3 / h; air flow rate is set to 4.35-4.45m 3 / h; the inlet water temperature is set to 20℃~22℃.

[0054] Example 1

[0055] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 21 parts by weight of carbon fiber reinforced PA; 13 parts by weight of E-glass fiber reinforced PA; 4 parts by weight of bio-based furanyl chloride derived aromatic polyamide resin; 7 parts by weight of polyether ester amide block copolymer; 1.2 parts by weight of talc filled PA; 1.7 parts by weight of montmorillonite powder; 0.35 parts by weight of aramid powder; 0.17 parts by weight of antioxidant 1098; and 0.57 parts by weight of coupling agent.

[0056] Comparative Example 1

[0057] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 23 weight parts of E-glass fiber reinforced PA; 14 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 7 weight parts of polyether ester amide block copolymer; 1.2 weight parts of talc filled PA; 1.7 weight parts of montmorillonite powder; 0.35 weight parts of aramid powder; 0.17 weight parts of antioxidant 1098; 0.57 weight parts of coupling agent.

[0058] Example 2

[0059] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 23 parts by weight of carbon fiber reinforced PA; 14 parts by weight of E-glass fiber reinforced PA; 5 parts by weight of bio-based furanyl chloride derived aromatic polyamide resin; 7 parts by weight of polyether ester amide block copolymer; 1.2 parts by weight of talc filled PA; 1.6 parts by weight of montmorillonite powder; 0.35 parts by weight of aramid powder; 0.18 parts by weight of antioxidant 1098; and 0.59 parts by weight of coupling agent.

[0060] Comparative Example 2

[0061] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 23 parts by weight of carbon fiber reinforced PA; 5 parts by weight of bio-based furanyl chloride derived aromatic polyamide resin; 17 parts by weight of polyether ester amide block copolymer; 1.2 parts by weight of talc filled PA; 1.6 parts by weight of montmorillonite powder; 0.35 parts by weight of aramid powder; 0.18 parts by weight of antioxidant 1098; and 0.59 parts by weight of coupling agent.

[0062] Example 3

[0063] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 20 weight parts of carbon fiber reinforced PA; 12 weight parts of E-glass fiber reinforced PA; 4 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 6 weight parts of polyether ester amide block copolymer; 1.2 weight parts of talc filled PA; 1.9 weight parts of montmorillonite powder; 0.32 weight parts of aramid powder; 0.19 weight parts of antioxidant 1098; 0.58 weight parts of coupling agent (montmorillonite powder, manganese powder and aramid powder together constitute nano-level wear-resistant additives, and the particle sizes are all between 80-100 nanometers).

[0064] Comparative Example 3

[0065] High-strength wear-resistant nylon, the raw materials of nylon and their weight parts are: 20 weight parts of carbon fiber reinforced PA; 12 weight parts of E-glass fiber reinforced PA; 4 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 6 weight parts of polyether ester amide block copolymer; 1.2 weight parts of talc filled PA; 1.9 weight parts of montmorillonite powder; 0.32 weight parts of aramid powder; 0.19 weight parts of antioxidant 1098; 0.58 weight parts of coupling agent (the particle sizes of montmorillonite powder, manganese powder and aramid powder are all between 200 and 300 nanometers).

[0066] A factory made finished nylon using the raw material formulas of Examples 1-3 and Comparative Examples 1-3 according to the processing technology of the present invention, and conducted flame retardant grade test, high temperature tensile test, compression modulus, impact elasticity, peel strength, water content, hardness, heat deformation temperature, melt index, thickness, combustion performance, compression permanent deformation and whiteness test on the nylon made therefrom. The experimental data are shown in Table 1 below:

[0067] Table 1

[0068]

[0069]

[0070] The effects of the raw material formula composition of Example 1 vs. Comparative Example 1, Example 2 vs. Comparative Example 2, and Example 3 vs. Comparative Example 3 on the performance of the nylon finished product are summarized as follows:

[0071] 1. Comparison of Example 1 Comparison of Comparative Example 1:

[0072] Example 1 uses 21 parts by weight of carbon fiber reinforced PA, while Comparative Example 1 does not use carbon fiber reinforced PA, but adds 2 parts by weight of E-glass fiber reinforced PA. It can be seen from the data in Table 1 that the carbon fiber reinforced PA makes the nylon finished product of Example 1 better than Comparative Example 1 in high temperature tensile strength and compression modulus performance. At the same time, Example 1 uses 4 parts by weight of bio-based furanoyl chloride derived aromatic polyamide resin, while Comparative Example 1 uses 14 parts by weight. The appropriate amount of bio-based furanoyl chloride derived aromatic polyamide resin in Example 1 can improve the heat resistance and dimensional stability of the material, but excessive addition in Comparative Example 1 will affect processing fluidity.

[0073] 2. Comparison between Example 2 and Comparative Example 2:

[0074] Example 2 uses 23 parts by weight of carbon fiber reinforced PA and 14 parts by weight of E-type glass fiber reinforced PA, while Comparative Example 2 uses 23 parts by weight of carbon fiber reinforced PA and 5 parts by weight of bio-based furanyl chloride-derived aromatic polyamide resin and 17 parts by weight of polyether ester amide block copolymer. The experimental data in Table 1 show that the rigidity and heat resistance of the nylon finished product of Example 2 are better than those of Comparative Example 2. Table 1 shows that the combination of carbon fiber reinforced PA and E-type glass fiber reinforced PA in the raw material formula helps to improve the rigidity and heat resistance of the finished product. At the same time, Example 2 uses 5 parts by weight of bio-based furanyl chloride-derived aromatic polyamide resin. amide resin and 7 parts by weight of polyetheresteramide block copolymer, while Comparative Example 2 used 5 parts by weight of bio-based furanyl chloride derived aromatic polyamide resin and 17 parts by weight of polyetheresteramide block copolymer. The experimental data in Table 1 show that the toughness and wear resistance of the nylon finished product of Example 2 are better than those of Comparative Example 2. Therefore, it is concluded that the combination of the reinforced polyamide resin and the polyetheresteramide block copolymer in the raw material formula ratio of Example 2 can improve the toughness and wear resistance of the material, but Comparative Example 2 lacks some reinforced polyamide resin, and excessive polyetheresteramide block copolymer will lead to increased material cost and increased processing difficulty.

[0075] 3. Comparison between Example 3 and Comparative Example 3:

[0076] The montmorillonite powder, manganese powder and aramid powder in Example 3 together constitute a nano-level wear-resistant additive, and the particle sizes are all between 80-100 nanometers, all reaching the nano level, while the particle sizes in Comparative Example 3 are all between 200-300 nanometers, all failing to reach the nano level. The data in Table 1 show that the wear resistance and mechanical properties of Example 3 are better than those of Comparative Example 3. Table 1 shows that the particle size of the nano-level wear-resistant additive helps to improve the wear resistance and mechanical properties of the nylon finished product, while the additive that does not reach the nano level cannot improve the wear resistance and mechanical properties of the nylon finished product.

[0077] In summary, the differences in raw material composition between Examples 1, 2, 3 and Comparative Examples 1, 2, 3 lead to different performance test results for different formulations, among which different combinations of nano-scale wear-resistant additives, carbon fiber reinforced PA and E-glass fiber reinforced PA, and changes in the addition amounts of bio-based furanyl chloride-derived aromatic polyamide resin and polyether ester amide block copolymer have different effects on the performance of the materials. The performance indicators of Examples 1-3 are all better than those of Comparative Examples 1-3, showing that the composite formulation of reinforced polyamide resin and nano-scale wear-resistant additives in the raw material formulation of the present invention can not only optimize the dispersibility and fusion of nylon finished products, but also improve the wear resistance and mechanical strength of the materials. Therefore, the formulation of the present invention is most effective in preparing high-strength wear-resistant nylon.

[0078] Example 4

[0079] The raw material formula of the invention is used and a twin-screw extrusion molding process is adopted to prepare the nylon finished product.

[0080] Comparative Example 4

[0081] The raw material formula of the invention is used and the melting and spinning technology is adopted to prepare the nylon finished product.

[0082] The molecular distribution and better mechanical properties of the nylon finished product prepared above were tested, and the data are shown in Table 2 below:

[0083] Table 2

[0084]

[0085]

[0086]

[0087] In summary, by comparing and analyzing Example 4 and Comparative Example 4, it can be seen that the test results of molecular distribution and multiple mechanical properties of Example 4 using the twin-screw extrusion molding process are better than those of Comparative Example 4 using the melting and spinning technology. This means that the twin-screw extrusion molding process used in the present invention can control the rheological properties of the material by setting the range of temperature, pressure and shear rate in advance, which not only makes the molecular distribution of the nylon finished product more uniform, but also makes the mechanical properties of the finished product reach the best.

[0088] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. High strength and wear-resistant nylon, characterized by: The raw materials of the nylon and their weight parts are: 20-23 weight parts of carbon fiber reinforced PA; 11-14 weight parts of E-glass fiber reinforced PA; 3-5 weight parts of bio-based furanyl chloride derived aromatic polyamide resin; 6-8 weight parts of polyether ester amide block copolymer; 1.1-1.3 weight parts of talc filled PA; 1.5-2.0 weight parts of montmorillonite powder; 0.30-0.36 weight parts of aramid powder; 0.16-0.20 weight parts of antioxidant 1098; 0.56-0.62 weight parts of coupling agent.

2. The high-strength wear-resistant nylon according to claim 1, characterized in that: The carbon fiber reinforced PA, E-glass fiber reinforced PA and talc powder filled PA together constitute a reinforced polyamide resin, and the montmorillonite powder, manganese powder and aramid powder together constitute a nano-level wear-resistant additive, and the particle size is between 80-100 nanometers.

3. The high-strength wear-resistant nylon according to claim 2, characterized in that: The synthesis process of the bio-based furanyl chloride-derived aromatic polyamide resin is as follows: S1.1, conducting a low-temperature solution polycondensation reaction of bio-based 2,5-furandicarbonyl chloride and 3,4'-diaminodiphenyl ether in a solvent volume ratio of 1:2 in 5-6 volumes of N,N-dimethylacetamide at 5-8°C; S1.

2. After the reaction is complete, the obtained resin solution is spun through a dry-jet wet spinning device using dry-jet wet spinning technology to prepare aromatic polyamide fibers containing furan rings.

4. The high-strength wear-resistant nylon according to claim 2, characterized in that: The polyether ester amide block copolymer is formed by connecting polyether and polyamide blocks through chemical bonds, and has a shrinkage rate of 0.5%-1.5%.

5. The processing technology of high-strength wear-resistant nylon is characterized by: The high-strength wear-resistant nylon according to claim 1 is prepared by parts by weight of the raw material, comprising the following steps: Step 1, raw material preparation: prepare raw material formula weight parts of bio-based furanyl chloride derived aromatic polyamide resin, polyether ester amide block copolymer, montmorillonite powder, manganese powder and aramid powder; Step 2, drying the raw materials: drying the bio-based furanyl chloride-derived aromatic polyamide resin and the polyether ester amide block copolymer; Step 3, mixing: uniformly mixing the dried bio-based furanoyl chloride-derived aromatic polyamide resin and the polyetheresteramide block copolymer with montmorillonite powder, manganese powder and aramid powder; Step 4: Extrusion molding: Use a twin-screw extruder for melt extrusion molding; Step 5: Extrusion process parameters: adjust the screw speed, feed screw speed, screw and barrel temperature and feed rate parameters; Step 6: Cooling and solidification: The molten material after extrusion is cooled and solidified through an air cooler to form the nylon shape designed by the manufacturer; Step 7. Post-processing: cutting, grinding or secondary processing of the extruded nylon according to the shape of the nylon; Step 8. Performance testing: Conduct flame retardant grade test, high temperature tensile test, compression modulus, impact elasticity, peel strength, moisture content, hardness, heat deformation temperature, melt index, thickness, combustion performance, compression permanent deformation and whiteness test on the manufactured nylon.

6. The processing technology of high-strength wear-resistant nylon according to claim 5 is characterized in that: In the step 2, the raw materials are dried: the bio-based furanyl chloride-derived aromatic polyamide resin is dried at 90-100° C. for 4-5 hours, and the polyether ester amide block copolymer is dried at 120-135° C. for 2-3 hours.

7. The processing technology of high-strength wear-resistant nylon according to claim 5, characterized in that: The stirring conditions of step three are: the stirring temperature is controlled at 50-60° C., the stirring speed is controlled at 200-250 r / min, and the stirring time is controlled at 1.5-3 hours.

8. The processing technology of high-strength wear-resistant nylon according to claim 5, characterized in that: The parameters of the twin-screw extruder melt extrusion molding in step 4 are set as follows: the extrusion temperature is controlled at 280-295°C, the pressure is controlled at 18-20MPa, and the shear rate is controlled at 300-400s -1 .

9. The processing technology of high-strength wear-resistant nylon according to claim 5, characterized in that: The extrusion process parameters in step 5 are set as follows: screw speed is 450-500r / min, feeding screw speed is 40-50r / min, screw temperature is 165°C-175°C, barrel temperature is 295°C-300°C, and feeding rate is 16-20kg / h.

10. The processing technology of high-strength wear-resistant nylon according to claim 5, characterized in that: In step 6, an air cooler is used for cooling and curing, and the parameters of the air cooler are set as follows: cooling capacity is 100kW; cooling water volume is set to 42-48m 3 / h; air flow rate is set to 4.35-4.45m 3 / h; the inlet water temperature is set to 20℃~22℃.